Comparative analysis of BSS-IBC, SW-PWM IBC and IBI-SW high efficiency converters - R. , Puviarasi; Maraim Bee, M. K.; Ramalingam, Mritha; M. , Saranya; D. , Dhanasekaran (International Journal of Psychosocial Rehabilitation, 2020)
The proposed work contributes to enhancing the efficiency of the the DC-DC Boost Converter in high-current and high-power applications. The main objective of the research is given as follows: To improve the efficiency of a DC-DC converter in high-power applications, a Bayes Soft Switching Interleaved Boost Converter (BSS-IBC) framework is designed. To identify the required number of parameters, such as power, voltage, and current ripple in the secondary layer soft switching, Naive Bayes classifiers are used in the proposed BSS-IBC framework. To minimize the converter switching time and improve the output voltage and current, an integrated framework of Sliding Window and Pulse Width Modulation (SW-PWM) is developed. The integrated interleaved and sliding windows (IBI-SW)-based PWM strategy is developed for the development of the effective DC-DC boost converter in a high-performance application. The incorporation of a MPPT algorithm is given in architecture to minimize switching noise and switching time.